The Information Technology's Impact on English Learning - Bukit, Herawati (Journal of Applied Linguistics, 2024)
Learning English could be greatly enhanced by Information Technology (IT). The function of IT in the context of learning English is covered in this article, along with topics such as multimedia-based learning, communication and cooperation, e-assessment, and independent learning. To gather the most recent data regarding the function of IT in English language learning, a literature review methodology is employed. The study's findings demonstrated that IT makes learning resources easily accessible, helps with English language learning applications, enhances the quality of learning with multimedia content, permits international communication and teamwork, makes evaluation and feedback procedures easier, and promotes independent learning. In summary, information technology significantly enhances the process of learning English. Keywords : Information_Technology; Impact; English_Learning